Peran Pondok Pesantren Dalam Membentuk Kemandirian Santri di Pondok Pesantren Al Manshuriyah Dono Arum Kecamatan Seputih Agung Kabupaten Lampung Tengah - Khusnul Khotimah; Hasyim As’ari; Wiwid Pratiwi (Berkala Ilmiah Pendidikan, 2024)
Pesantren is a traditional Islamic educational institution in which there are students who live together and study under the guidance of kyai and ustadz, and have a dormitory as a place for the students to stay. Islamic boarding schools generally teach various kinds of religious knowledge, social sciences and other sciences. The elements of Islamic boarding schools consist of huts, mosques, students and kyai. However. Not all students have an independent attitude, students who do not have self-confidence tend to live dependent on other people. A qualitative research technique is used in this sort of study. This study makes use of both primary and secondary resources for its data. Observation, interviews, and documentation are the methods used to gather data. The study that has been conducted has led to the conclusion that: Some of the efforts made by the Al Manshuriyah Dono Arum Islamic Boarding School, Seputih Agung District, Central Lampung Regency, include using effective methods, namely by getting used to taking care of their own needs, learning several skills and learning to blend in with society.